A interação na sala de aula de língua estrangeira - Bullio, Paula Cristina [UNESP]; Del Ré, Alessandra [UNESP] (My University, 2010)
The world we have been living in has adopted competition as the way for surviving in it, especially due to the capitalism and consumer habits. In this research speaking English is considered one of these differentiations, i.e., distinguishing individuals a unique people. In addition, it is expected that by using this language, among other things, people could have access to: education, a better job and a higher quality of life. However, the process of learning a foreign language is very complex caused by many features that are involved in it, e.g. the impossibility to dissociate language, culture and society. Moreover, it was contemplated if from this language learning, it would be possible to build social and ideological relations as well as personal identities. The most applicable conclusion of this research is the requisite of making students aware of the process for an effective foreign language learning. As a consequence, the context and social, cultural, and ideological characteristics that are part of the mother tongue society must be taken into consideration in the same way as the foreign language society.

Atualmente, vivemos em um mundo globalizado em que a competição é uma das bases de seu funcionamento. Busca-se, assim, obter um diferencial que, aqui, consideramos ser a Língua Estrangeira (no caso, o inglês) e, por meio dela, esperase, entre outras coisas, ter acesso à educação, melhor emprego e qualidade de vida. Entretanto, o processo de aprendizagem de uma LE é bastante complexo devido a inúmeros aspectos que o permeiam. Entre eles, podemos apontar a relação indissociável entre língua, cultura e sociedade. Deste modo, observamos e analisamos as diferentes interações na sala de aula de inglês e as implicações neste processo. A conclusão mais relevante deste artigo é a necessidade de tornar os alunos conscientes do processo de aprendizagem efetiva de uma LE, levando em conta o contexto e os aspectos sociais, culturais e ideológicos que permeiam tanto a sociedade de sua LM, como a da LE.
The process of interaction in the foreign language classroom
Keywords: English Learning; Classroom; Interaction; Adults; Aprendizagem de inglês; Sala de aula; Interação